2005
DOI: 10.1002/car.925
|View full text |Cite
|
Sign up to set email alerts
|

Using computer‐assisted self‐interviewing (CASI) questionnaires to facilitate consultation and participation with vulnerable young people

Abstract: This paper explores computer-assisted self-interviewing (CASI) as a methodology for consulting with vulnerable children. The authors provide a brief review of the literature in this area, indicating that computer-mediated environments for self-administered questionnaires can be particularly helpful in enabling data to be obtained about sensitive subjects. A case example is provided of Viewpoint Interactive, a CASI application in use in the UK in local authority children's services, education, and in learning d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…There are two approaches involving computers, broadly categorized as computer assisted self-interviewing (CASI) and computer-assisted interviewing (CAI). CASI (sometimes called computer-assisted personal interviewing) involves the individual completing a questionnaire on a computer without assistance (Davies & Morgan, 2005) and is often used to survey highly sensitive issues. Black and Ponirakis (2000) found that the anonymity offered by this method encouraged adolescents to respond to questions about sensitive topics such as drug and alcohol use or sexual experience.…”
mentioning
confidence: 99%
“…There are two approaches involving computers, broadly categorized as computer assisted self-interviewing (CASI) and computer-assisted interviewing (CAI). CASI (sometimes called computer-assisted personal interviewing) involves the individual completing a questionnaire on a computer without assistance (Davies & Morgan, 2005) and is often used to survey highly sensitive issues. Black and Ponirakis (2000) found that the anonymity offered by this method encouraged adolescents to respond to questions about sensitive topics such as drug and alcohol use or sexual experience.…”
mentioning
confidence: 99%
“…However, in efforts to ease data collection within a school setting, future tool adaptations could be supported by including voice narrations to accompany assessments. Whether the preference is to have a researcher narrate or the narration to come from a virtual platform, this feature of the tool could prove particularly useful for younger children in answering assessment questions without having to rely solely on their own reading skills (e.g., audio, computer-assisted, self-interviewing; Davies & Morgan, 2005). Similarly, and like many of the mentioned tools, future or adapted tools might include guided prompts that provide definitions or examples of gender diversity prior to measuring gender identity (Temkin et al, 2017).…”
Section: General Conclusion On Child-reported Gender Measuresmentioning
confidence: 99%
“…Another promising tool to use in regular follow-up in social work with OHC children is Computer-Assisted Self interviewing (M. Davies & Morgan, 2005), which has shown to be well accepted by OHC children in the UK (Morgan & Fraser, 2009). A recent development is the highly modular "MyView-app" (W. Davies, 2020), developed by the Viewpoint organization and used in UK, Ireland, Western Australia (Garsed & Davies), and Canada.…”
Section: Recommendations To Practicementioning
confidence: 99%